Historical epidemiology of hepatitis C virus (HCV) in select countries – volume 2. (January 2015) - Saraswat, V.; Norris, S.; de Knegt, R. J.; Sanchez Avila, J. F.; Sonderup, M.; Zuckerman, E.; Arkkila, P.; Stedman, C.; Acharya, S.; Aho, I.; Anand, A. C.; Andersson, M. I.; et al.
Summary: Chronic hepatitis C virus (HCV) infection is a leading cause of liver related morbidity and mortality. In many countries, there is a lack of comprehensive epidemiological data that are crucial in implementing disease control measures as new treatment options become available. Published literature, unpublished data and expert consensus were used to determine key parameters, including prevalence, viremia, genotype and the number of patients diagnosed and treated. In this study of 15 countries, viremic prevalence ranged from 0.13% in the Netherlands to 2.91% in Russia. The largest viremic populations were in India (8 666 000 cases) and Russia (4 162 000 cases). In most countries, males had a higher rate of infections, likely due to higher rates of injection drug use (IDU). Estimates characterizing the infected population are critical to focus screening and treatment efforts as new therapeutic options become available.